2017
DOI: 10.12662/2317-3076jhbs.v5i1.1012.p56-61.2017
|View full text |Cite
|
Sign up to set email alerts
|

Perfil epidemiológico dos casos de sífilis congênita em um município de médio porte no nordeste brasileiro

Abstract: Introdução: A sífilis congênita é ocasionada pela transmissão vertical da bactéria, Treponema pallidum, ou seja, da gestante para o concepto por via transplacentária. É considerada como sendo um sério problema de saúde pública. Objetivo: Analisar o perfil epidemiológico dos casos de sífilis congênita no município de Sobral, Ceará. Metodologia: Levantamento epidemiológico, descritivo utilizando dados secundários com abordagem quantitativa. Os dados foram coletados a partir das notificações do Sistema de Informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
77

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(94 citation statements)
references
References 1 publication
2
15
0
77
Order By: Relevance
“…Many CS cases would have been prevented if the MoH recommendations for SiP were fully adopted. Other Brazilian studies also showed that prenatal care did not ensure an early SiP diagnosis, nor the timely and adequate treatment of pregnant women and their sexual partners, and did not prevent miscarriages, stillbirths, and deaths related to CS [3][4][5][6][7][8][9][10] . In SP state, from 2007 to 2014, there were 1,012 fetal losses due to CS (126 deaths, and 886 miscarriages and stillbirths) 5 .…”
mentioning
confidence: 99%
“…Many CS cases would have been prevented if the MoH recommendations for SiP were fully adopted. Other Brazilian studies also showed that prenatal care did not ensure an early SiP diagnosis, nor the timely and adequate treatment of pregnant women and their sexual partners, and did not prevent miscarriages, stillbirths, and deaths related to CS [3][4][5][6][7][8][9][10] . In SP state, from 2007 to 2014, there were 1,012 fetal losses due to CS (126 deaths, and 886 miscarriages and stillbirths) 5 .…”
mentioning
confidence: 99%
“…The number of unknowns went from zero in 2012 to 76 in 2015, increasing more than the number of partners who got treatment. Lima et al (2017) and Souza et al (2016) presented similar congenital syphilis data in Sobral (State of Ceará) and in Brazil, respectively. Those numbers go against gainsay of Teixeira et al (2015) in Chapadão do Sul (State of Minas Gerais), where 50% of partners were treated with the pregnant and, among those who did not be treated, the reason was unknown.…”
Section: Resultsmentioning
confidence: 65%
“…Regarding race and schooling, results were comparable to the data from São Paulo state. 6,18 Higher frequency was observed for Caucasian pregnant women (57%) with incomplete elementary schooling (27%). As for occupation, 46% of the Unknown/blank 20 6.90 continue pregnant women were referred to as housewives, in agreement to other studies, 14,15 although this information is often overlooked in the forms.…”
Section: Discussionmentioning
confidence: 98%